2021
DOI: 10.1093/neuros/nyab222
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Trans-Stenotic Blood Flow Velocity Differences and the Cerebral Venous Pressure Gradient in Transverse Sinus Stenosis: A Prospective 4-Dimensional Flow Magnetic Resonance Imaging Study

Abstract: BACKGROUND The relationship between trans-stenotic blood flow velocity differences and the cerebral venous pressure gradient (CVPG) in transverse sinus (TS) stenosis (TSS) has not been studied. OBJECTIVE To evaluate the hemodynamic manifestations of TSS and the relationship between trans-stenotic blood flow velocity differences and the CVPG. METHODS Thirty-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 22 publications
3
33
2
Order By: Relevance
“…Compared to the only previous imaging study that investigated subjects with diverticulum independently, the V mn detected by the current RCCD technique closely conforms to the results measured by 4D MR ( Li et al, 2021 ), with 7.3% difference in V mn ( Table 6 ); nonetheless, a stark difference in V max is found between their and our results. Additionally, ITSS in this study was also found uncorrelated with the hemodynamic parameters, which is antithetical to the study of Ding et al (2021) , since the Doppler insonation plane was more distant from the center of TSS, from which the sinus flow velocity can decelerate after issuing from a TSS. We reckon that these study discrepancies predominantly result from the fundamental difference in the selection of region/point of interest.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Compared to the only previous imaging study that investigated subjects with diverticulum independently, the V mn detected by the current RCCD technique closely conforms to the results measured by 4D MR ( Li et al, 2021 ), with 7.3% difference in V mn ( Table 6 ); nonetheless, a stark difference in V max is found between their and our results. Additionally, ITSS in this study was also found uncorrelated with the hemodynamic parameters, which is antithetical to the study of Ding et al (2021) , since the Doppler insonation plane was more distant from the center of TSS, from which the sinus flow velocity can decelerate after issuing from a TSS. We reckon that these study discrepancies predominantly result from the fundamental difference in the selection of region/point of interest.…”
Section: Discussionsupporting
confidence: 66%
“…Venous PT is characterized by the reduction or elimination of a vascular sound when the ipsilateral internal jugular vein (IJV) is compressed ( Mattox and Hudgins, 2008 ; Grewal et al, 2014 ). In addition, anatomical abnormalities related to the structural integrity of the sigmoid plate and the vascular shape are often revealed using imaging modalities ( Dong et al, 2015 ; Cummins et al, 2021 ; Ding et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A jet-like flow in the stenosis and downstream of the stenosis was observed in all patients with transverse sinus stenosis. Since increased prevalence of sigmoid sinus diverticulum/dehiscence and transverse sinus stenosis in idiopathic intracranial hypertension did not correlate with the presence of pulsatile tinnitus in another study [ 78 ], there are probably other hemodynamic factors such as intra-stenotic maximum velocity dependent on the local trans-stenotic pressure gradient and complex flow patterns, such as vortex flow, turbulent flow, and helical flow, that are better correlated with pulsatile tinnitus [ 79 ].…”
Section: Management Of Iihmentioning
confidence: 99%
“… 1 , 10 , 11 In addition to SSWAs, hemodynamic perturbations in the transverse‐sigmoid sinus are considered to contribute to increases in the volume of vascular sound. 10 Such perturbations include: (1) excessive flow kinetic energy in the form of transverse‐sigmoid sinus enlargement (TSSE) or sigmoid sinus ectasia, 5 , 10 , 12 , 13 (2) flow obstructions such as transverse sinus stenosis (TSS) and arachnoid granulation, 14 , 15 , 16 , 17 , 18 and (3) idiopathic intracranial hypertension (IIH). 8 Despite a convoluted relationship among PT, SSWAs, and flow pathologies, the incidence of SSWAs is higher in patients with IIH than in healthy controls and the general PT population.…”
Section: Introductionmentioning
confidence: 99%